Perubahan Kurikulum di Indonesia: Dinamika Implementasi Kurikulum 2013 menuju Kurikulum Merdeka di Madrasah Ibtidaiyah - Titi Anriani; Nining Surya Ningsih; Putri Sekar Sari; Esty Cahyaningsih; Sedya Santosa (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This research was conducted to understand the dynamics of curriculum implementation in Madrasah Ibtidaiyah as a result of curriculum changes that always occur. The type of research used in this study is qualitative, focusing on the case study method. Data collection techniques were carried out using two data sources, namely primary data and secondary data. Data collection methods through observation, interviews, and documentation. Data analysis through the process of condensation, presentation, and finally conclusion/verification. The data that has been analyzed will be tested for validity using data triangulation. The research subjects were the Head of Madrasah, the curriculum coordinator, and the teachers. The results of this study indicate that the implementation of the Curriculum in Madrasah Ibtidaiyah is faced with various complex challenges, ranging from stakeholder readiness, preparation of learning tools, and mastery of technology, to mindset and adaptation. Continuous efforts need to be made to improve the understanding, skills and readiness of stakeholders in dealing with this curriculum change. Research needs to be conducted in various madrasahs and levels to find out the obstacles and solutions in implementing the new curriculum. The goal is for madrasahs to be able to implement various types of curriculum in the future well and optimally.